Anticipatory Consumptions - Guo, Liang (Management Science, 2020)
Mental simulations such as anticipatory and/or retrospective emotions can yield higher weight for a delayed consequence than for current well-being (i.e., negative devaluing). In this research, we investigate the behavioral and welfare implications of negative devaluing for intertemporal consumptions in an intrapersonal game. Our general framework accounts for two distinctions: desired versus undesired consumptions, and naive versus sophisticated beliefs about future selves’ preferences. Naive people procrastinate desired consumptions and preproperate undesired ones. The behavior of sophisticated people generally exhibits a cyclical pattern. Sophistication may either mitigate or exacerbate the time-inconsistency problem, and hence may improve or undermine long-run welfare, depending on the valence and the units of consumptions and on whether consumptions are tied consecutively. In addition, our comparative statics analysis generates surprising results with respect to the impacts of decision parameters (e.g., deadline, consumption units). We also discuss implications for targeted pricing, product design, promotion strategies, and savings. This paper was accepted by Matthew Shum, marketing.